Analysis Of The Effectiveness Of The Self Assimilation Program During The Covid-19 Pandemic (Review Of Permenkumham Number 43 Year 2021) - Denna Destian Prakasa Wibowo; Meysita Arum Nugroho (LEGAL BRIEF, 2022)
The determination of the Public Health Emergency and the Covid-19 Pandemic Outbreak as a national disaster by the Government has an impact on other policies from the government that must be issued in order to maintain national stability. One of them is the Minister of Law and Human Rights Regulation No. 10 of 2020 which regulates the independent assimilation policy for prisoners on the grounds of overcapacity in prisons and is also expected to be an alternative to minimize the spread of Covid-19. The Permenkumham was even extended for two amendments, namely Permenkumham No.32 of 2020 and Permenkumham No.43 of 2021. This study aims to analyze the effectiveness of the assimilation program in several Indonesian prisons based onPermenkumham stipulated.This research is a normative legal research with a sociological juridical approach related to actual problems related to the Effectiveness of the Independent Assimilation Program in the Covid-19 Pandemic Period. Some of the conclusions reached include: 1) Permenkumham No. 43 of 2021 does not provide assimilation rights to prisoners of terrorism, narcotics, corruptors, other serious crimes, and prisoners who repeat a crime; 2) that the implementationindependent assimilation program in the midst of prison overcapacity is only a temporary solution, alternative non-prison punishment such as supervision and community service is seen as more efficient than prison law because it can achieve the goal of coaching; 3)Some of the obstacles in implementing the assimilation program during the COVID-19 pandemic, namely the negative public view of ex-convicts, Pokmas support that has not been maximized, and not all prisoners have a clear family background.